Digitized AGONSA Method: Its Effectiveness on the Word Problem Skill Involving Addition of Grade 1 Learners - Honey Gwen Penedez; Aiyana Varron; Chedhy Mae V. Oberez; Diane Mae P. Ulanday-Lozano; Jovar G. Pantao; Precy M. Regalado (NAJAHA, 2026)
Mathematical word problem-solving is an important skill in early education however, many learners still struggle with numerical reasoning and reading comprehension. This study examined the effectiveness of the Digitized AGONSA Method in improving the addition word problem-solving skills of Grade 1 learners during the School Year 2025–2026. Using a single-experimental research design, thirty (30) purposively selected learners from Pedro Acharon Sr. Central Elementary School participated in the study. Findings revealed that learners improved from an “Emerging (Low Proficient)” level before the intervention to a “Transitioning (Proficient)” level after using the Digitized AGONSA Method. Statistical analysis also showed a significant difference between the pretest and posttest results, confirming the effectiveness of the intervention. The study concluded that the Digitized AGONSA Method effectively enhanced learners’ addition word problem-solving skills and may be integrated into classroom instruction. Hence, the study recommends integrating the Digitized AGONSA Method into classroom instruction with the support of administrators, teachers, and coordinators, as well as exploring its application in other mathematical topics, grade levels, and comparative studies. Keywords: digitized learning, AGONSA Method, word problem-solving skills, addition, Grade 1 learners